Working, Housing: Urbanizing The International Year of Global Understanding - IYGU - Robinson, Jennifer; Scott, Allen J.; Taylor, Peter J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents an incisive outline of the historical development and geography of cities. It focuses on three themes that constitute essential foundations for any understanding of urban form and function. These are: (a) the shifting patterns of urbanization through historical time, (b) the role of cities as centers of production and work in a globalizing world, and (c) the diverse housing and shelter needs of urban populations. The book also explores a number of critical urban problems and the political challenges that they pose. Empirical evidence from urban situations on all five continents is brought into play throughout the discussion. .
Cities in Time and Space -- Working -- Housing -- Conclusion Remarks: Urbanization -- the Future.
Keywords: Sociology, Urban; Labor economics; Human geography; Regionalism; Urban Sociology; Labor Economics; Human Geography; Regionalism